A colour recognition device for the visually disabled people - Norazila Othman; Mohd Zarhamdy Md. Zain; Iskandar Shah Ishak; Abdul Rahim Abu Bakar; Mastura Ab Wahid; Maziah Mohamad (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
Visually disabled people rely on the sense of touch and sense of hearing to help them recognise anything in their everyday life. Colours, however, is also important in giving information about things such as the colour of cash note (blue, green, red, orange and purple), the colour of spices (yellow turmeric, red chilli, green chilli) and colour of cloth. Without a sense of visual, they are not able to recognise colour and perceive the beauty of colour. This study was conducted to develop a colour recognizer for visually ‎disabled people‎. Colour recogniser used the colour sensor to sense the colour, microcontroller to recognise the colour and notify the user using a speech generator and speaker. The device is powered by dry cell batteries and designed to be user-friendly, practical and portable. The testing is done to show that this device was able to sense and differentiate 12 primary colours in the RGB colour wheel and validated the accuracy of this devices.